FAKTOR- FAKTOR YANG MEMPENGARUHI PENYUSUNAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH BERBASIS KINERJA DI PEMERINTAH KOTA SORONG - Jumame, Santrinita Trh.; Karamoy, Herman; Poputra, Agus T (Universitas Sam Ratulangi, 2015)
The objective of this is to test empirically and analyze whether commitment factor of all organizational component, perfection of administration system, enough human resources, transparent reward and firm punishment have an effect on budgeting of regional revenue and expenditure based on performance. The population on this research are the chiefs of work unit of regional public service and the chief of planning division of work unit of regional public service in government of Kota Sorong regency that amount to 70 person, where all of them become the sample. To test hypothesis of commitment influence ,of all organization component. the perfection of administration system, sufficient human resources, transparent reward, and firm punishment have effect on budgeting of regional revenue and expenditure (APBD) based on performance simultaneously and partially used F test and tÂ test. The result of this research proves thatÂ the commitment of all organization component, the perfection of administration system, sufficient human resources, transparent reward and firm punishment have an effect on significant budgeting of regional revenue and expenditure (APBD) based on performance simultaneously, but the one the end partiallyÂ the perfection of administration system, sufficient human resources ,transparent reward the biggest influence to budgeting of regional revenue and expenditure (APBD) based on performance is the perfection of administration system.